Song Leader Competence Improvement Training in Voting and Reading Numbers Notations Buku Ende on Sunday Worship at HKBP BETESDA - Algoboy Nelson Nainggolan; Junita Batubara; Daniel Purba; Yolasrida Lubis (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Thematic Field Practice is one of educational activities that must be taken by every college student. Thematic Field Practices are aimed to guide students to become professional educators, responsible, disciplined, and know the proper procedures. The purpose of this Thematic Field Practice is to increase student experience, insight, and skills in the field of music and share insights learned while studying at HKBP Nommensen University Medan to the HKBP BETESDA song leader. During the Thematic Field Practice (PLT) there are several of the song leader members who had difficulty singing and reading the notation in the Buku Ende. So students do an easier training method, namely by singing the correct notation at a slow tempo, after the song leader members understand how to read the correct notation. According to the author's observation, the results for the song leader participants are to increase their knowledge in singing, gain insight into reading rhythm and notation in the Buku Ende and increase the confidence of the song leader members when singing.